PILATES EXERCISES VS CONVENTIONAL EXERCISES ON FUNCTIONAL DISABILITY AND PAIN WITH LUMBAR SPONDYLOSIS - Rayjade, Amrutkuvar; Chintamani, Radhika; Yadav, Trupti (International Journal of Psychosocial Rehabilitation, 2020)
Lumbar spondylosis isa degenerative condition. Approximately 70-90% of population suffers from low back pain secondary to lumbar spondylosis. This inhibits an individual from leading an active life style and often also affects their day to day activities severely.Pilate’s is a system that has been created to improve balance, strength and flexibility which may help counter the effects of lumbar spondylosis.Objectives: To find and compare the effectiveness of Pilate’s exercises and conventional exercises on pain and useful handicap in subjects with lumbar spondylosis.Methods: 30 subjects diagnosed as Lumbar spondylosis with lower back pain having symptoms for more than 3 months were included for the investigation on the basis of inclusion and exclusion criteria. In the study pre and post treatment outcome assessment was taken on Visual Analogue Scale (VAS),Schober test and on Modifiedoswestry low back pain questionnaire (MODQ). Intermittent lumbar traction, Short wave diathermy, Interferential therapy were baseline treatment for both the group. Group A received baseline treatment and Pilates exercises protocol and Group B received baseline treatment and conventional exercise protocol for4 weeks treatment protocol. Results: Intra group and inter group comparison results demonstrated measurably huge improvement in post interventional VAS, Schober test, MODQ score for both groups. Conclusion: Group A and B both shown enormous improvement in post interventional VAS, Schober test, MODQ score. There was no noteworthy contrast between the effect of two therapeutic methods on pain and utilitarian incapacity in both groups had same effect.